HAK MENGUASAI NEGARA DALAM SISTEM TATA KELOLA MINYAK DAN GAS BUMI: ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 36/PUU-X/2012 - Nizammudin Nizammudin (Jurnal Hukum dan Peradilan, 2016)
The Constitutional Court Decision No. 36 / PUU-X / 2012 concerning the unconstitutionality of BP Migas in Law No. 22 of 2001 on Oil and Gas has provoked public debate about the management systems of Indonesian oil and gas. This study focuses on the following questions: First, what the meaning and the concept of the state control rights of oil and gas under the 1945 Constitution of The Republic of Indonesia?; Second, what what are the legal consequences of the Constitutional Court Decision No. 36/PUU-X/2012 on the national oil and gas management policy?. The results of the study shows the following conclusions. First, the concept of state’s rights in Article 33 of the 1945 Constitution of the Republic of Indonesia philosophically derived from the construction of Pancasila which empowers the state to involve in the management of natural resources in order to provide the prosperity of the people, but at the same time providing opportunities for private ownership as far as not to degrade the state's role in determining the decision-making and policy-making. Secondly, the Constitutional Court Decision No. 36/PUU-X/2012 does not limit the authority of the Government and the Parliament to form any oil and gas administrative body to the extent not contrary to the options proposed by the Constitutional Court, i.e. the state-owned enterprises or the government. The term ‘government’ in the legal consideration of the Constitutional Court has a much broader meaning and should not be limited to the Ministry of Energy, but also includes the SOE itself or an independent agency that may be established by the government based on the law.Keywords: state’s rights, administration, oil and gas, Constitutional Court